Servant leadership through arts – a state of the art - Barroca, Ana (2017)
The future leaders are growing in the digital era and through a profound crisis. These future leaders demand for purpose, meaning and connection and they will be working in organisations also shaped by the globalisation of knowledge, markets and customers and the information and communication technology. The Artful Leadership project aims at developing the new generation of servant leaders through arts. The Erasmus + Programme co-funded the Artful Leadership consortium to research and develop new learning resources that can empower a leadership shift. The research phase allowed the project consortium to explore the main drivers changing society, business and learning and to ask which model of leadership will be more suitable to live and be successful today and in the future; as well as, which tools could be more effective to reach and engage future leaders through a learning journey and disrupting with the onetime training event. The approach to servant leadership was subsequent and allowed to understand the background, its main characteristics and what the impact when experienced in different organisations is. Finally, arts based learning concept, characteristics and good practices were explored focusing on the impact it brings when applied into management and leadership educational programs.